(untitled) (Archive of Conferences, 2020)
Endemic species of the Scutellaria L. family, widespread in Uzbekistan, are found mainly in mountainous regions. Depending on their occurrence in the mountainous region, they were divided into 3 zones: low-mountain (2 species), mid-mountain (6 species), high-mountain (3 species).